Gut microbiota characteristics and therapeutic effects of fecal microbiota transplantation in children with autism spectrum disorder in central China: a combined cross-sectional and prospective study - Wu, Rui; Teng, Xu; Guo, Yunkai; Cai, Yongxi; Lv, Yongling; Gao, Heyun; Zhang, Wen; Shen, Hexiao; Fan, Jingyi (Frontiers in Pediatrics, 2025)
IntroductionGut microbiota dysbiosis is implicated in autism spectrum disorder (ASD), yet scalable therapeutic interventions remain limited. This study investigated gut dysbiosis profiles in children with ASD and evaluated the clinical efficacy of a simplified fecal microbiota transplantation (FMT) protocol using pediatric donors.MethodsIn a cross-sectional phase, 48 children with ASD and 51 age-/sex-matched healthy controls underwent gut microbiota analysis. Subsequently, 25 ASD participants received FMT via a streamlined protocol: 3-day bowel preparation followed by 6-day transcolonoscopic microbiota infusion from pediatric donors. Clinical outcomes and microbiota shifts were assessed at 3-month follow-up.Results(1) Baseline Dysbiosis: ASD subjects exhibited reduced microbial diversity, with decreased Faecalibacterium and Bifidobacterium but elevated Megamonas and Akkermansia vs. controls. (2) Clinical Efficacy: Post-FMT, significant improvements occurred in core ASD symptoms and gastrointestinal comorbidities. (3) Microbiota Shifts: FMT recipients showed increased beneficial genera (Prevotella, Faecalibacterium, Agathobacter, Dorea) and reduced Escherichia-Shigella.DiscussionA simplified pediatric donor FMT protocol effectively modulates gut microbiota composition and alleviates both behavioral and gastrointestinal symptoms in children with ASD. This strategy demonstrates feasibility for clinical translation, highlighting microbiota-targeted therapy as a promising intervention for ASD.